Developing Online Teaching Materials for Science Subject During Covid-19 Era - Nurhikmah H; Abdul Hakim; Dedi Kuswandi; Sulfianti Sulfianti; Sujarwo Sujarwo (Graduate School of Universitas Negeri Malang, 2021)
Abstract: Research aims (1) to develop online teaching materials (2) to design online teaching materials (3) to determine the validity, practicality, and effectiveness of online teaching materials for science subjects in grade V SD Negeri 32 Bungloe, Bantaeng Regency during Covid-19 era. This used Research and development methods (R & D) which is focused on developing online teaching materials using flipbooks. The ADDIE model consists of 5 stages, namely: analysis, development, implementation, and evaluation. The results showed that the online teaching materials using the developed flipbook were declared valid, where the validation of the material and the media obtained very valid category results. The results of the assessment of respondents in small group trials and teacher responses to teaching material products were very practical, it can be seen from the responses of students and teachers who obtained the very practical category. The development of online teaching materials that are effectively developed, It can be seen from the average learning outcome recapitulation that there is an increase of student learning outcomes between before and after the use of online teaching materials.Abstrak: Tujuan penelitian (1) mengembangkan bahan ajar online, (2) mendesain bahan ajar online, dan (3) mengetahui kevalidan, kepraktisan, dan keefektifan bahan ajar online mata pelajaran IPA di kelas V SD Negeri 32 Bungloe Kabupaten Bantaeng di Era Covid 19. Metode penelitian pengembangan (Researh and Development/R&D) yang difokuskan untuk mengembangkan bahan ajar online dengan menggunakan flipbook. Model ADDIE yang terdiri atas lima tahap, yaitu analisis (analysis), desain (design) pengembangan (development), implementasi (implementation), dan evalusai (evaluation). Hasil penelitian menunjukkan bahwa bahan ajar online menggunakan flipbook yang dikembangkan dinyatakan valid, dimana validasi materi ddan media memperoleh hasil kategori sangat valid. Hasil penilaian responden uji coba kelompok kecil dan tanggapan guru terhadap produk bahan ajar dinyatakan sangat praktis dilihat dari respon siswa dan guru yang memperoleh kategori sangat praktis. Pengembangan bahan ajar online yang dikembangkan efektif dilihat dari rata-rata rekapitulasi hasil belajar menunjukakan adanya peningkatan hasil belajar siswa antara sebelum dan sesudah penggunaan bahan ajar online.